Physics responsible for heating efficiency and self-controlled temperature rise of magnetic nanoparticles in magnetic hyperthermia therapy - Shaterabadi, Zhila; Nabiyouni, Gholamreza; Soleymani, Meysam (Progress in biophysics and molecular biology, 2018)
Magnetic nanoparticles as heat-generating nanosources in hyperthermia treatment are still faced with many drawbacks for achieving sufficient clinical potential. In this context, increase in heating ability of magnetic nanoparticles in a biologically safe alternating magnetic field and also approach to a precise control on temperature rise are two challenging subjects so that a significant part of researchers’ efforts has been devoted to them. Since a deep understanding of Physics concepts of heat generation by magnetic nanoparticles is essential to develop hyperthermia as a cancer treatment with non-adverse side effects, this review focuses on different mechanisms responsible for heat dissipation in a radio frequency magnetic field. Moreover, particular attention is given to ferrite-based nanoparticles because of their suitability in radio frequency magnetic fields. Also, the key role of Curie temperature in suppressing undesired temperature rise is highlighted. [Display omitted] •In MHT, the heat generated by MNPs is produced by independent mechanisms.•MHT demands MNPs with high heating efficiency in a safe alternating magnetic field.•Undesired temperature rise can be inhibited through Curie temperature of MNPs.•This review discusses about the Physics concepts involved in the above subjects.